Evaluasi Kekuatan Resistance Spot Welding pada Proses Tailor welded blankss Menggunakan Mill-steel Beda Ketebalan - Khoirudin khoirudin; Dicky Dimyati; Apang Djafar Ashiedieque; Sukarman S; Fathan Mubina Dewadi; Nana Rahdiana; Istianto Budhi Rahardja; Anwar Ilmar Ramadhan; Heri Suripto (Universitas Muhammadiyah Magelang, 2021)
This paper presented the test of cup drawing, and the tensile ability of tailor welded blanks (TWBs) used to join the resistance spot welding a variety of different parameters. This study used SPCC-SD (JIS 3141) material with a material thickness of 1.0 mm and 1.2 mm. This research is focused on obtaining the highest tensile-shear strength of resistance spot welding and how it affects the results of the drawing cup process. This study used an experimental research method using six samples of RSW parameters. RSW parameters used are welding current, welding time, and squeeze time. This research was achieved the highest tensile-shear strength value of 5.09 kN and the lowest 4.15 kN which was achieved in the 5th and 1st samples respectively. The results of the cup drawing test using RSW parameters in the 5th and 6th samples showed no TWB failure in the welded area. Further research will be carried out by performing Taguchi optimization using RSW and TWBs parameters in the cup drawing process.